Sistem Pakar Diagnosa Penyakit Kura-Kura menggunakan Metode Forward Chaining - Melda Agnes Manuhutu; Christy Christy (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Expert systems are widely applied in disease diagnosis, yet research on diagnosing turtle diseases remains limited, despite turtles being highly susceptible to bacterial, viral, and metabolic disorders that are difficult to identify due to non-specific symptoms. This study aims to design and build a web-based expert system for diagnosing turtle diseases using the Forward Chaining method. The system was developed using the Agile approach, covering literature study, expert data collection, system design, implementation, testing, and evaluation, and was built with PHP, MySQL, and Bootstrap. Knowledge data was obtained from interviews with experienced reptile veterinarians and relevant literature, resulting in three turtle diseases and ten symptoms compiled into an IF-THEN rule base. Black box testing showed that all eight test scenarios functioned as expected, indicating 100% system functionality. Accuracy testing by experts showed an accuracy rate of 88.89%. These findings indicate that the developed expert system can serve as a reliable preliminary diagnostic tool to support turtle owners, veterinarians, and conservation efforts.